2020
DOI: 10.1055/a-1250-8078
|View full text |Cite
|
Sign up to set email alerts
|

Vergleich der Kahnbeinrekonstruktion mit einem nicht-vaskularisierten Knochentransplantat mit und ohne intraoperativer Stoßwellenanwendung – vorläufige Ergebnisse

Abstract: Zusammenfassung Hintergrund/Ziel Eine hochenergetische, fokussierte Stoßwellenbehandlung (ESWT) stimuliert die Knochenheilung durch Neo-Angiogenese und Aktivierung von Osteozyten. Diese Studie untersucht, ob durch eine intraoperative ESWT die Heilungsrate bei Rekonstruktion des Kahnbeins bei Pseudarthrose mittels nicht-gefäßgestieltem Knochentransplantat verbessert oder beschleunigt werden kann. Patienten und Methoden In einer noch laufenden prospektiven Studie werden Patienten mit Rekonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…3,4,7 Relevant studies in humans reveal that ESWT remains safe, increases blood flow within the uninjured scaphoid, and may accelerate bone healing in patients receiving non-vascularized bone grafts for reconstruction of scaphoid nonunion. [8][9][10] Our preliminary findings support the safety and utility of ESWT in pediatric craniofacial surgery and contribute to the growing body of evidence regarding various treatment regimens.…”
Section: Discussionsupporting
confidence: 62%
“…3,4,7 Relevant studies in humans reveal that ESWT remains safe, increases blood flow within the uninjured scaphoid, and may accelerate bone healing in patients receiving non-vascularized bone grafts for reconstruction of scaphoid nonunion. [8][9][10] Our preliminary findings support the safety and utility of ESWT in pediatric craniofacial surgery and contribute to the growing body of evidence regarding various treatment regimens.…”
Section: Discussionsupporting
confidence: 62%
“…In a recent randomized study, the authors examined the impact of one dose of intraoperatively administered electrical bone stimulation following ORIF with nonvascularized bone graft among scaphoid nonunion patients; the addition of bone stimulator resulted in a greater proportion of healed patients by 12 weeks postoperatively. 21 Bone stimulators have also been used to accelerate bone healing among acute scaphoid fractures; Mayr et al 22 compared the effects of adjunctive bone stimulation (ultrasound) on acute fracture healing and found radiographic healing in the experimental group at 43 days compared with 62 days in the control group; this was statistically significant. Hannemann et al 23,24 demonstrated similar findings among acute scaphoid fractures treated with pulsed electromagnetic bone stimulation.…”
Section: Discussionmentioning
confidence: 99%